Choosing a future for epidemiology: II. From black box to Chinese boxes and eco-epidemiology. - Susser, M (1996)
Part I of this paper traced the evolution of modern epidemiology in terms of three eras, each with its dominant paradigm, culminating in the present era of chronic disease epidemiology with its paradigm, the black box. This paper sees the close of the present era and foresees a new era of eco-epidemiology in which the deployment of a different paradigm will be crucial. Here a paradigm is advocated for the emergent era. Encompassing many levels of organization--molecular and societal as well as individual--this paradigm, termed Chinese boxes, aims to integrate more than a single level in design, analysis, and interpretation. Such a paradigm could sustain and refine a public health-oriented epidemiology. But preventing a decline of creative epidemiology in this new era will require more than a cogent scientific paradigm. Attention will have to be paid to the social processes that foster a cohesive and humane discipline.